Analysis of urea pyrolysis in 132.5–190 °C. (15th April 2019) - Wang, Denghui; Dong, Ning; Hui, Shien; Niu, Yanqing
Abstract: Urea pyrolysis in the temperature range from 132.5 to 190 °C was studied in a self-designed fixed-bed experimental system, and the products in solid and gaseous phases were systematically analysed by a liquid chromatography-mass spectrometer (LC-MS) and an online mass spectrometer (MS), respectively. Experimental results showed that in 132.5–160 °C, urea was only involved in consumption reactions. The formation reactions of biuret and cyanuric acid (CYA) rather than the decomposition reaction of urea occupied the main part of urea consumption. Above 160 °C, the dominant reaction of CYA turned from formation to decomposition, while the conversion temperature point of biuret was 170 °C. The NH3 production fluctuated in 132.5–170 °C but kept rising in 170–190 °C. The decomposition reaction of biuret above 170 °C accounted for the sustained rising. The HNCO production decreased from 132.5 to 160 °C but increased from 160 to 190 °C. The decomposition of CYA in 160–190 °C was responsible for the decrease. The detailed analysis data and related discussion of urea pyrolysis pathways in 132.5–190 °C contributed to the efficient utilization of urea in low-temperature urea-SCR process.